EFEKTIFITAS PENGEMBANGAN MODUL BERBASIS BUDAYA DAERAH PESISIR SELATAN SUMATERA BARAT - Syafni Gustina Sari; Ira Rahmayuni Jusar (Cerdas Proklamator, 2019)
Education and life is a relationship between process and content, namely the process of cultural takeover in the sense of civilizing humans, another aspect of the function of education is to process culture into mental attitudes, behavior, and even the personality of students. Based on the Kompas news quote, the problem that occurs a sense of pride and concern for preserving culture is less embedded in Indonesia's young generation today. Their interest to learn it is lacking (Kompas, 2018) This has an impact on schools, one of the most important elements in schools is students. Students are less familiar with culture, especially the culture in the environment they live. Therefore it is necessary to develop a culture-based module in the Pesisir Selatan so that students do not only consider mathematics only abstract but also concrete. The purpose of this study is to see the effectiveness of using culture-based modules. This type of research is research and development (R&D). effectiveness is obtained by providing a test of learning outcomes after the use of regional culture-based modules. From the research results, it is found that the use of culture-based modules is very effective.